EVALUASI PROGRAM PRAKTIK INDUSTRI PRODI PENDIDIKAN TEKNIK OTOMOTIF FT UNY - Pambayun, Nirmala Adhi Yoga; Retnowati, Trie Hartiti (Universitas Negeri Yogyakarta, 2024)
Internship programs play an important role in developing student competencies to meet the expectations of the working world. Internship programs need to be evaluated to maintain or improve their quality. This study aims to evaluate the achievement of the objectives of the Internship programs in the Automotive Engineering Education Department Faculty of Engineering Universitas Negeri Yogyakarta. This research is included in goal-oriented evaluation research (goal oriented model). The respondents to this study are students of the Automotive Engineering Education Study Program who have implemented industrial practices in 2022. Data was collected by questionnaires and interviews. Questionnaires are used to measure the achievement of industrial practice objectives while interviews are used for qualitative deepening of the results obtained from quantitative data. Quantitative data analysis techniques use descriptive statistics while qualitative data is summarized and synthesized and then spelled out clearly, and concisely. The results of the evaluation show that, 1) The objectives of Internship programs in general is included into the category of sufficient achievement; 2) There are 4 goals out of a total of 8 goals that included into the category of sufficient achievement, and 4 other goals fall into the category of high achievement; 3) A very significant factor causing the non-achievement of internship program goals is the Covid-19 pandemic which causes lectures to be carried out online so that student competencies are not sufficient to follow internship program.